Designing of the business model in creative industries – preliminary research results - Kasprzak, Rafał; Tomaszewski, Albert; Ziółkowska, Marta (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The paper presents the preliminary results of research on the specifics of the operationalization of the business model in creative industries. The issue of business models in creative industries is an emerging research area. The authors argue that the potential associated with adopting business model optics to creative industries is very large. Obtained results of preliminary studies indicate elements of the business model relevant in creative industries and confirm the validity of the assumptions made and research activities carried out.